PENGARUH PEMBERIAN PAKAN YANG BERBEDA TERHADAP LAJU PERTUMBUHAN IKAN LELE (Clarias gariepinus) - Febry Ramadhani; M Rizki; Friska Hernita; Namirah Yasmine Raudah (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2023)
Catfish is one of the cultivation commodities that has various advantages, including fast growth and high adaptability to the environment. Catfish (Clarias sp.) is one of the six other commodities, namely seaweed, catfish, milkfish, tilapia and grouper whose cultivation development will be accelerated with the aim of increasing aquaculture production in the next few years. The method used is an experimental method based on direct observation. The data analysis used is by conducting experiments based on direct observation in the field. The results obtained show that the catfish has a total body length of 30 cm, has a gut length of 15 cm, has a 3:1 ratio of the difference in feed given.